Vladavina prava kao vladavina ljudskih prava / The Rule of Law as the Rule of Human Rights - Nurkić, Benjamin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
The text is a review of the book Ka filozofiji prava kao filozofiji ljudskih prava written by Jasminka Hasanbegović and published by Dosije studio, Belgrade, 2021.